Wear and corrosion studies of duplex surface-treated AISI-304 steel by a combination of cathodic cage plasma nitriding and PVD-TiN coating. Issue 15 (1st August 2022) - Naeem, M.; Awan, Shabana; Shafiq, M.; Raza, H.A.; Iqbal, Javed; Díaz-Guillén, J.C.; Sousa, R.R.M.; Jelani, Mohsan; Abrar, M.
Abstract: This work aims to improve the surface properties of AISI-304 austenite stainless steel by using duplex treatment of cathodic cage plasma nitriding (CCPN) and PVD-TiN, and the results are compared with individual treated samples. This combination of treatments is used to improve the inherent drawbacks of individual PVD deposited TiN, such as voids, cracks, and detachment of hard layer from steel due to significant differences in the hardness of steel and hard layer. The hardness of steel (1.9 GPa) is improved to 17 GPa, 12 GPa, and 22 GPa by using only TiN, CCPN, and duplex treatment. The only TiN deposited sample shows the formation of layer with intense diffraction peaks along (311) and (400) orientation, and its orientation changed with intense peaks along (111), (200), and (220) by using duplex treatment, which increases the hardness. Furthermore, the wear resistance is improved by all treatments, specifically by using duplex treatment. While using a ball-on-disc wear tester, the TiN layer is not detached from the substrate in the duplex treated sample, in contrast with the only TiN sample. Furthermore, the corrosion rates are reduced by using the duplex treatment and the appliance of plasma nitriding before the TiN fills the voids and cracks in layer, and thus, the duplex layer effectively prevents steel against corrosive environment. This study suggests that combining these treatments improves surface hardness, wear resistance, and corrosion resistance.